2011
DOI: 10.5424/fs/20112003-10982
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sampling methods to estimate structure

Abstract: Aleppo pine had a large forest cover in North Africa and along the Mediterranean basin which management is not fully developed and new forest tools are required. In this research, the forest structure, epidometric characteristics and allometric relationships were studied in 79 plots covering four bioclimatic zones from natural even aged forests of Aleppo pine located between eastern Algeria to the western coastal part of Tunisia. To characterize the forest structure three sampling methods were carried out: cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…In other forest areas of Aleppo pines, Harfouche et al (2003) reported an increase in mean individual seed mass related to a coastal gradient on the Mediterranean coast of North Africa, but this was due to the confounding effect of latitudinal effects. A negative elevation effect on cone size was found in this study, confirming the previous results obtained by Ayari et al (2011b) in the forests of northeastern Tunisia, Boulli et al (2001) in Aleppo pine forests in Morocco and Climent et al (2008) in many Mediterranean countries, including Tunisia. In this study, the production of wood, cones and seeds were altitude sensitive; these results were confirmed by Ayari et al (2011c) who showed that the predictive models obtained showed that the elevation had an effect on the size of the cone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other forest areas of Aleppo pines, Harfouche et al (2003) reported an increase in mean individual seed mass related to a coastal gradient on the Mediterranean coast of North Africa, but this was due to the confounding effect of latitudinal effects. A negative elevation effect on cone size was found in this study, confirming the previous results obtained by Ayari et al (2011b) in the forests of northeastern Tunisia, Boulli et al (2001) in Aleppo pine forests in Morocco and Climent et al (2008) in many Mediterranean countries, including Tunisia. In this study, the production of wood, cones and seeds were altitude sensitive; these results were confirmed by Ayari et al (2011c) who showed that the predictive models obtained showed that the elevation had an effect on the size of the cone.…”
Section: Discussionsupporting
confidence: 92%
“…Our research shows that altitude is negatively correlated with the production of Aleppo pine to sub-humid bioclimate; these results are not in agreement with Turner et al (2007) who showed for a similar species, Pinus contorta, the positive effect of elevation on cone/seed production that was attributed to shorter drought periods associated with more abundant rainfall. Our study show that exposure north, north-east, north-west, south, south-east, south-west have a positive correlation with the production of wood, cones and seeds, which confirm the findings of Ayari et al (2011b), showing favourable cone harvesting and seed yield in forests on favourable aspects, such as north-east, south-east south and north-west This could be explained by the higher availability of light and temperatures during the pollination period, which seems to play a major role in promoting conifer breeding success in the same way as other species (Hylander, 2005). Our results do not support the results of Schiller and Atzmon (2009) who concluded that higher egg abortions and lower pollen vigour and viability were found in the north, south, south-west and west aspects, favouring subsequent mortality from cone formation or leading to empty seeds (Schiller, Atzmon, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, longitudinal gradients represent the strongest geographical determinant causing a marked increase in cone dimensions and seed content, mainly in the semiarid zone. High consistency was found regarding the effect of elevation and longitude on cone dimensions and average individual seed mass (Ayari et al 2011b). The effect of the geographical distribution on fructification is greater under drought conditions (Schiller & Atzmon 2009).…”
Section: Suggestions To Enhance Seed Productionmentioning
confidence: 76%
“…One hectare of Aleppo pine forest in the Kef region, Tunisia, was estimated to produce 400 kg of cones every three years, corresponding to 10 kg seeds (cone to seed yield is 2.5% -MARHPT 2015). Ayari et al (2011b) showed that the weight of seeds per cones was 1.72 g in a sub-humid area, while it was 1.12-1.53 g in a semi-arid area. In comparison, seed production was 261.5 g tree -1 in a subhumid area, while it was 118.4-166.2 g tree -1 in a semi-arid area.…”
Section: Production Of Cones and Seedsmentioning
confidence: 98%
See 1 more Smart Citation